Not Yet Post-Colonial : Essays on Ghetto Being, Cosmology and Space in Post-Imperial Zimbabwe - Kapuya, Zvikomborero (Book collections on Project MUSE., 2020)
The epistemic deficiency of contending issue in post-imperial Africa, Zimbabwe in particular influence the author to take readers on the interesting journey of joining the reflections of ghetto life into concept and culture. Ghetto renaissance responding to ghetto condition proved itself to the future, Cultural Revolution confronting Afro-fascist nationalist regimes and the complex global coloniality. Though some challenges, such as identity crisis, self-hate and criminal activities, ghetto cosmology left no stone unturned in making the post-colonial Zimbabwe a practical political project in the prism of decoloniality.